DIGITAL TRANSFORMATION, OPEN INNOVATION AND DYNAMIC CAPABILITIES THEORY: PROPOSAL OF A DIGITAL MATURITY DIAGNOSTIC MODEL FOR A PUBLIC ORGANIZATION: PROPOSTA DE UM MODELO DE DIAGNÓSTICO DE MATURIDADE DIGITAL PARA UMA ORGANIZAÇÃO PÚBLICA (ESMAT Magazine, 2025)
This study examines the relevance of open innovation and dynamic capabilities theory in assessing and enhancing digital transformation in the public sector. The main objective is to develop a digital maturity diagnostic model grounded in these concepts, enabling organizations to evaluate their practices and implement improvements. The research employs a mixed bibliographic review methodology, supported by artificial intelligence tools for organizing and analyzing studies. The proposed model incorporates a questionnaire and a visual framework to support the evaluation and interpretation of digital maturity. The expected contribution is to foster innovation and organizational transformation in public administration within a dynamic environment marked by disruptive technologies and complex emerging challenges.
Keywords: Digital Maturity; Open Innovation; Dynamic Capabilities; Artificial Intelligence; Public Administration